2009
DOI: 10.1111/j.1464-410x.2009.08496.x
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless percutaneous nephrolithotomy: 3 years of experience with 454 patients

Abstract: OBJECTIVE To present our experience with 454 patients who had tubeless percutaneous nephrolithotomy (TPCNL) over last 3 years. PATIENTS AND METHODS From September 2004 to August 2007, all patients aged >14 years and undergoing PCNL were considered for TPCNL. Exclusion criteria were the presence of pyonephrosis, matrix calculi, significant bleeding or residual stone burden and need for three of more percutaneous accesses. These patients had a nephrostomy tube placed after PCNL (control group). The remaining pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
5
46
1
2
Order By: Relevance
“…Recent studies showed that PCNL procedures performed without tubes decreased the hospital stay significantly. [26,27] In our study, the mean hospital stay was 4.57±2.1 days in the PCNL group and 1.56±0.8 days in the RIRS group. Similar to the literature results, hospital stay was significantly shorter in the RIRS group compared with the PCNL group (p<0.001).…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies showed that PCNL procedures performed without tubes decreased the hospital stay significantly. [26,27] In our study, the mean hospital stay was 4.57±2.1 days in the PCNL group and 1.56±0.8 days in the RIRS group. Similar to the literature results, hospital stay was significantly shorter in the RIRS group compared with the PCNL group (p<0.001).…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have shown that tubeless PCNL is the most important factor in decreasing hospital stay. 18,19 However, the decision to position a tubeless PCNL is surgeon's choice and intraoperative findings. It can be applied in the absence of a significant residual stone, pelvicaliceal system perforation, and significant bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…Tubeless PCNL has been a successful procedure even in advanced aged patients. [13,14] Shah et al [15] documented superiority of percutaneous nephrolithotomy in terms of patient's satisfaction. They reached a conclusion that PCNL was a safe technique even in solitary kidney, past history of any ipsilateral renal surgical procedure, elevated serum creatinine levels, with an advantage of bilateral simultaneous use of PCNL or contralateral endourological removal of stones.…”
Section: Discussionmentioning
confidence: 99%